Bacterial Count of Pasteurized Milk Packed by Plastic Distributed in Malang Municipality (Jurnal Ilmu dan Teknologi Hasil Ternak, 2007)
The objective of study was to investigated the number of bacteria in pasteurized milk packed by plastic and distributed in Malang Municipality. The results were compared with the standards, then. The material consisted of six different products obtained from six milk pasteurized agents. A survey research was carried out, and sampling of pasteurized milk was taken by simple random sampling and the agent was taken as total sampling. The number and type of bacteria were determined in the laboratory. TPC method was used to test the number of bacteria, MPN method on coliform bacteria, Gram colouring on bacterial identification, and TPC method on the number of bacteria in plastic packaging. Data were descriptively analysed. Compared with standard of pasteurized milk quality according to the standard regulated by government. The results showed the pasteurized milk packed by plastic distributed in Malang Municipality was unsuitable according to the standards with bacterial content and still found the coliform bacteria. It is recommended the need of agency which enable to control and testing for the products in Malang Municipality to keep quality and safety for the consument. Â  Keywords : bacterial count, pasteurized milk, plastic packaging.